2000
DOI: 10.20955/wp.2000.010
|View full text |Cite
|
Sign up to set email alerts
|

Perfecting the Market's Knowledge of Monetary Policy

Abstract: The rational expectations revolution made clear that a complete macro model requires a specification of the government's economic policy. We argue that monetary policy should be conducted in such a way that the market can predict policy actions. An implication of market success in predicting policy actions is that interest rates move ahead of the policy actions, and such a timing relationship may appear to some as the central bank following the market instead of leading it. Another implication of the market pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
75
0
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(82 citation statements)
references
References 5 publications
6
75
0
1
Order By: Relevance
“…8 Such practice is well in line with the recent evidence that unanticipated changes in the federal funds rate affect the financial markets while anticipated changes in the federal funds rate have little effect (e.g., Poole and Rasche 2000;Kuttner 2005 andWongswan 2009). Most previous studies on news announcements tend to apply Ordinary Least Squares (OLS) estimator to serve the purpose.…”
Section: Basic Regression Resultsmentioning
confidence: 56%
“…8 Such practice is well in line with the recent evidence that unanticipated changes in the federal funds rate affect the financial markets while anticipated changes in the federal funds rate have little effect (e.g., Poole and Rasche 2000;Kuttner 2005 andWongswan 2009). Most previous studies on news announcements tend to apply Ordinary Least Squares (OLS) estimator to serve the purpose.…”
Section: Basic Regression Resultsmentioning
confidence: 56%
“…109 Although recent, this literature is voluminous. Representative works are: Blinder et al (2001), Broaddus (2001), Freedman (2002, , Guthrie and Wright (2000), Kohn and Sack (2003), Lange et al (2001), Poole and Rasche (2000), Poole et al (2002), Sellon (2002), and Woodford (2002). 110 FOMC transcripts, January 30-31, 1996, Appendix-Kohn Statement.…”
Section: The Making Of Us Monetary Policy 1979-1999mentioning
confidence: 99%
“…They checked the impact of expected and un-expected interest rates and found that un-expected policy changes have a significant impact on both aggregate and sectoral returns. Poole and Rasche (2000) also used change in FED funds future rate to generate the monetary policy shocks. Rapallo (1998) used a structural VAR model to analyze the impact of monetary policy changes on European stock markets (Holland, Norway, Italy, Germany, Austria, Belgium, France, Spain, Sweden and Switzerland).…”
Section: Literature Reviewmentioning
confidence: 99%
“…They highlighted the fact that market participants take their financial decisions by considering the expected policy actions. Bernanke and Kuttner (2005), Poole and Rasche (2000), Berument et al (2007), Bredin et al (2005), Gregoriou et al (2009), used Kuttner's (2001) futures methodology where federal funds rate changes were decomposed into expected and unexpected interest rates to analyze the impact of Monetary Policy shocks on US stock returns.…”
Section: Introductionmentioning
confidence: 99%